Kedisiplinan Lansia dalam Pencegahan Covid-19 di Desa Situraja Utara, Kecamatan Situraja, Sumedang - Rifiana, Andi Julia; Novianti, Silvia (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The elderly are at high risk of being infected with the Covid-19 virus. This study aims to determine the factors related to the discipline of the elderly in preventing Covid-19 in North Situraja Village, Situraja District, Sumedang Regency, West Java. This type of research was analytic with a cross-sectional design. The research subjects were 65 elderly who were selected by simple random sampling technique. Data were collected through filling out a questionnaire, then analyzed using the Chi-square test. The results of the analysis show that the majority of the elderly was undisciplined (55.4%), the highest level of knowledge was not good (58.5%), the highest attitude was negative (61.5%), the highest level of anxiety was not anxious (52.3%), the majority of the elderly did not have the availability of facilities (60%) and the majority of the elderly believed in Covid-19 (60%). The results of the analysis of the hypothesis test showed the p-value for each factor, namely knowledge = 0.000, attitude = 0.001, anxiety = 0.020, availability of facilities = 0.047 and perception of Covid-19 = 0.000. Furthermore, it was concluded that there was a significant relationship between knowledge, attitudes, anxiety, availability of facilities and perceptions with the discipline of the elderly in preventing Covid-19. It is hoped that the elderly will be able to attend the elderly posyandu so that they can receive good information regarding the prevention of Covid-19.Keywords: Covid-19; elderly; prevention; disciplineABSTRAK Para lansia berisiko tinggi terinfeksi virus Covid-19. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan kedisiplinan lansia dalam pencegahan Covid-19 di Desa Situraja Utara, Kecamatan Situraja, Kabupaten Sumedang, Jawa Barat. Jenis penelitian ini adalah analitik dengan desain cross-sectional. Subyek penelitian adalah 65 lansia yang dipilih dengan teknik simple random sampling. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan bahwa mayoritas lansia tidak disiplin (55,4%), tingkat pengetahuan terbanyak adalah kurang baik (58,5%), sikap terbanyak adalah negatif (61,5%), tingkat kecemasan terbanyak adalah tidak cemas (52,3%), mayoritas lansia tidak memiliki ketersediaan sarana (60%) dan mayoritas lansia percaya Covid-19 (60%). Hasil analisis uji hipotesis menunjukkan nilai p untuk masing-masing faktor yaitu pengetahuan = 0,000, sikap = 0,001, kecemasan = 0,020, ketersediaan sarana = 0,047 dan persepsi terhadap Covid-19 = 0,000. Selanjutnya disimpulkan bahwa terdapat hubungan yang signifikan antara pengetahuan, sikap, kecemasan, ketersediaan sarana dan presepsi dengan kedisiplinan lansia dalam pencegahan Covid-19. Diharapkan lansia untuk bisa mengikuti posyandu lansia agar dapat menerima ifnormasi yang baik terkait pencegahan Covid-19.Kata kunci: Covid-19; lansia; pencegahan; kedisiplinan